2020
DOI: 10.3389/fimmu.2020.584423
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Infiltrating Effector Memory Antigen-Specific CD8+ T Cells Predict Response to Immune Checkpoint Therapy

Abstract: Immune checkpoint therapy (ICT) results in durable responses in individuals with some cancers, but not all patients respond to treatment. ICT improves CD8 + cytotoxic T lymphocyte (CTL) function, but changes in tumor antigen-specific CTLs post-ICT that correlate with successful responses have not been well characterized. Here, we studied murine tumor models with dichotomous responses to ICT. We tracked tumor antigen-specific CTL frequencies and phenotype before and after ICT in respondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 68 publications
2
37
2
Order By: Relevance
“…Among TILs, CD8+ T cells are the main subset of CTLs and play vital roles in tumor eradication. CD8+ T cells, as well as their subset CD8+ central memory T cells (Tcm) and CD8+ effector memory T cells (Tem), represented significantly higher scores in HPV-positive HNSCCs than in other groups, indicating a highly activated CTL function in the TME of HPV-positive HNSCCs 17 , 18 . Consistent with our results, accumulating evidence suggests that HPV-positive HNSCCs correlate with T cell-enriched TME, increased T cell receptor pathway signaling, activated cytotoxic capacity, and viral antigen-specific CD8+ T cell infiltration into the TME 19 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Among TILs, CD8+ T cells are the main subset of CTLs and play vital roles in tumor eradication. CD8+ T cells, as well as their subset CD8+ central memory T cells (Tcm) and CD8+ effector memory T cells (Tem), represented significantly higher scores in HPV-positive HNSCCs than in other groups, indicating a highly activated CTL function in the TME of HPV-positive HNSCCs 17 , 18 . Consistent with our results, accumulating evidence suggests that HPV-positive HNSCCs correlate with T cell-enriched TME, increased T cell receptor pathway signaling, activated cytotoxic capacity, and viral antigen-specific CD8+ T cell infiltration into the TME 19 21 .…”
Section: Discussionmentioning
confidence: 99%
“…However, PD-1 + cells were not the only cell type to receive influence from TCF1. PD-1 − CD8 + T MPECs were also found to be dependent on the expression of TCF1, and the conditional deletion of Tcf7 in MPECs compromised their ability to respond to ICB therapy [ 7 , 89 ]. Interestingly enough; however, observations in melanoma patients reported that only the expression of both TCF7 and PDCD1 in CD8 + T cells correlated with improved patient survival rates [ 8 ].…”
Section: Icb As a Methods Of T Cell Reinvigorationmentioning
confidence: 99%
“…Among TILs, CD8 + T cells are the main subset of CTLs and play vital roles in tumor eradication. CD8 + T cells, as well as their subset CD8 + central memory T cells (Tcm) and CD8 + effector memory T cells (Tem), presented signi cantly higher scores in HPV-positive HNSCCs than in other groups, indicating a highly activated CTL function in the TME of HPV-positive HNSCCs 17,18 .…”
Section: Discussionmentioning
confidence: 99%